2011
DOI: 10.1111/j.1365-2109.2011.02846.x
|View full text |Cite
|
Sign up to set email alerts
|

Spirulina meal has acted as a strong feeding attractant for Litopenaeus vannamei at a very low dietary inclusion level

Abstract: The present work aimed at studying the growth performance and feeding preference of Litopenaeus vannamei juveniles fed on diets supplemented or not with Spirulina meal. Litopenaeus vannamei juveniles (3.89 AE 0.25 g) were stocked for 72 days in 28 round 500-L tanks at 44 shrimp/tank (77 juveniles/m 2 ). The diets were supplemented with 0.5% of a commercial feed attractant (C25 and C50) or with Spirulina meal (S25 and S50). In C25/S25 and C50/S50 there were reductions of 25% and 50% in ¢shmeal inclusion level r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 11 publications
0
25
0
Order By: Relevance
“…Moreover, feed intake (g/fish) of our three-spot gourami tended to increase with dietary Spirulina levels from 2.5 to 10 %, which is comparable to reported results in the cichlids (P. acei) fed 10 % of Spirulina in diet and showed a significantly higher feed intake value (12.5 g/fish) compared to control (9.63 g/fish) (Guroy et al 2012). Such trends may be linked to the stimulating attractive compounds in Spirulina meal that can improve feed intake and, consequently, boost the fish growth, survival, and feed efficiency (Promya and Chitmant 2011;Fernandes Silva-Neto et al 2012). This was previously demonstrated in ornamental fish species (guppy and platy) with greater intake rates for Spirulina-based diets than for dietary fungus and Azolla (Scaria et al 2000) as well as in white-leg shrimp (Litopenaeus vannamei) (Fernandes Silva-Neto et al 2012).…”
Section: Discussion Growth Performance and Survivalmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, feed intake (g/fish) of our three-spot gourami tended to increase with dietary Spirulina levels from 2.5 to 10 %, which is comparable to reported results in the cichlids (P. acei) fed 10 % of Spirulina in diet and showed a significantly higher feed intake value (12.5 g/fish) compared to control (9.63 g/fish) (Guroy et al 2012). Such trends may be linked to the stimulating attractive compounds in Spirulina meal that can improve feed intake and, consequently, boost the fish growth, survival, and feed efficiency (Promya and Chitmant 2011;Fernandes Silva-Neto et al 2012). This was previously demonstrated in ornamental fish species (guppy and platy) with greater intake rates for Spirulina-based diets than for dietary fungus and Azolla (Scaria et al 2000) as well as in white-leg shrimp (Litopenaeus vannamei) (Fernandes Silva-Neto et al 2012).…”
Section: Discussion Growth Performance and Survivalmentioning
confidence: 99%
“…Such trends may be linked to the stimulating attractive compounds in Spirulina meal that can improve feed intake and, consequently, boost the fish growth, survival, and feed efficiency (Promya and Chitmant 2011;Fernandes Silva-Neto et al 2012). This was previously demonstrated in ornamental fish species (guppy and platy) with greater intake rates for Spirulina-based diets than for dietary fungus and Azolla (Scaria et al 2000) as well as in white-leg shrimp (Litopenaeus vannamei) (Fernandes Silva-Neto et al 2012). …”
Section: Discussion Growth Performance and Survivalmentioning
confidence: 99%
“…Both the algae used in this study have been reported as a good source of HUFA (Volkman et al, 1989) in addition to usual nutrient sources available in algae namely protein, lipids, carbohydrates vitamins and minerals (Ju et al, 2012). Microalgae also act as feed attractant and carotenoid sources (Regunathan and Wesley, 2006;Silva-Neto et al, 2012) Healthy phytoplankton bloom in water is also provide proper turbidity and subsequently stabilize the shrimp.…”
Section: Discussionmentioning
confidence: 96%
“…Feeding rates were based on the formula MM = 0.0931BW 0.6200 , where MM is the maximum amount of feed that can be eaten daily by one individual per body weight (BW; Nunes & Parsons, ). This equation has been successfully applied to estimate daily feeding rates of L. vannamei (Lemos & Nunes, ; Nunes, Sá, Carvalho, & Sabry‐Neto, ; Silva‐Neto, Nunes, Sabry‐Neto, & Sá, ). In the first 14 days of rearing, meals were adjusted on a daily basis following an estimated weight gain of 100 mg day −1 shrimp −1 and a 0.5% weekly drop in shrimp survival across all diets.…”
Section: Methodsmentioning
confidence: 99%